تطوير مهارة الكتابة باللغة العربية لطلاب جامعة الرانيري الإسلامية الحكومية - A. Latif, Hamdiah (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2023)
This article would like to discuss about the topic on how to increase capacity in writing skills in Arabic language among students of the Islamic State University (UIN) Ar-Raniry Banda Aceh, especially students of the Tarbiyah Faculty, Arabic Language Teaching Study Program. Writing skills is one of the most difficult skills to be developed in its application, even though the theory and material presented by the lecturers about it, tends to make it easier during the teaching and learning process. This article attempts to examine the precise and easy steps that can be taken in increasing Arabic writing capacity and skills among university students. This article uses qualitative methods to diagnose various factors and problems faced by students when writing exercises are applied, and this article also tries its best to offer the right methods to make it easier for students to develop writing and composing skills (in Arabic language).